Effects of beak trimming on the performance, beak length, behavior, and carcass traits of a local broiler breed reared in battery cages. (1st July 2020) - Li, Junying; Chen, Hong; Dai, Cong; Sa, Renna; Wang, Zhicheng; Wang, Jiangxian; Su, Hu; He, Xinxin; Guo, Xing; Jiang, Runshen
Abstract: This study investigated the effects of beak trimming on a local broiler breed. A total of 648 one‐day‐old birds were randomly allocated into three treatments: no trimming (NBT), infrared beak trimming (IRBT), and hot‐blade beak trimming (HBBT). The performance, beak length, behavior, carcass traits, organ percentages, and meat quality were inspected. The body weight (BW) from 7 to 35 days in the IRBT group was significantly lower than that in the NBT group, and the BW from 7 to 49 days was lower than that in the HBBT group ( p <  .05). Compared with untrimmed birds, birds in the IRBT group had lower average daily feed intake (ADFI) from 15 to 21 days, and higher heart percentage and L* value in the breast muscle. The upper beak length at 28 and 49 days of age were longest in untrimmed birds, intermediate in birds in the HBBT group, and shortest in the IRBT groups ( p  <.05). No evidence was found that HBBT caused changes in performance, behavior, carcass traits, organ percentages, and meat quality except for lower change in spleen percentage. Taken together, IRBT had more influence at inhibiting early BW, ADFI, and upper beak length than HBBT in the local broiler breed.